Investigation of protein and carbohydrate components of extracellular polymeric substances in the sludges having pin floc characteristics and their role in dewaterability - Yıldırımlı, Aslı. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2005., 2005)
In this research, protein and carbohydrate components of extracellular polymeric substances of the non settling sludges having pin floc characteristics and the role of EPS components were investigated. The results of pin floc sludges compared with waste activated sludges. Five different sludge samples were analyzed. The three pin floc sludge samples were obtained from sequencing batch raector, aerobic pond and facultative ponds of Bursa Hamitler Leachate Traetment Plant respectively. One of the samples was grown in the bench-scale batch reactor in laboratory and the other sample was obtained from a raw pharmaceutical industry wastewater treatment plant. Extracellular polymeric substances of sludge samples were extracted by a cation exchange resin at a dosage of 75 g/g VSS (volatile suspended solids). The dewatering characteristics of the sludge samples were determined by measuring the filterability in terms of capillary suction time and specific resistance time to filtration and compactibility in terms of cake solids concentration. The floc structures of sludge samples were also observed microscopically. The result of observations showed sludges having microflocs (pin flocs) have very high EPSp values compared to lab-grown sludge and typical waste activated sludges. Their EPSc/EPSp values were also low leading to very poor settling and dewatering properties. It seems that protein component of EPS may have an effect on the pinfloc (microfloc) formation and it deteriorates the sludge dewaterability and settleability. Compactibility, in terms of cake solids concentration, increased by decreasing concentrations of EPSprotein. Filterability, in terms of specific resistance to filtration, increased considerably by increasing concentrations of EPSprotein. Sludge samples having pin floc characteristics had very high SRF values compared to the samples of typical waste activated sludge. High SRF values indicate the difficulty of the sludge to be filtered. During the SRF experiments, filtration time for pin floc sludges were too long. On the other hand samples of typical WAS were filtered easily.
Keywords: Polymers.; Polymers and polymerization.; Chemical reactions.